Optimalisasi Biosorpsi Bekatul Terhadap Kalsium (Ca) dengan Menggunakan Metode Batch - Subarman Subarman; Asri Saleh; Aisyah Aisyah (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2013)
The study is titled Optimization of biosorption Biomass Against Calcium (Ca) by using the method of Batch. Background on this research that, the utilization of biomass as an adsorbent bran on the absorption of calcium metal (Ca) and reduce the pollution caused from the bran biomass. This study aims to determine the optimum pH and time as well as processing of biomass with metal biosorption Calcium (Ca). Bran biomass taken directly to rice mills in Kecematan Pallangga Gowa. The method used in this study is the activation process, the determination of the optimum pH, optimum timing, method in the determination of biosorption Batch, then the results were analyzed by using Atomic absorption spectrophotometer (AAS).The results obtained from this study is that the pH optimum at pH 9, the optimum contact time to 15 minutes, and the biosorption capacity of 14.1804 mg/L.